Comparative study for degradation of Congo red dye from synthetic wastewater by photocatalytic redox reactions using various nanoscale semiconductors - Jassim, Rusul A.; Abbas, Ammar S. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
A comparative study for two nanoscale semiconductors (TiO2 and WO3) was conducted as heterogeneous photocatalysts to degrade about 50 ppm of Congo red dye in an aqueous solution. The reaction was carried out in a batch reactor placed in a dark box and equipped with an air pump. The dye solution and 0.2 g/L of the catalyst were mixed, firstly, in a dark environment to monitor the amount of adsorbed dye, then the ultraviolet light was turned on with two different powers (15 and 30 W) to study the photocatalytic degradation reactions. The results showed that TiO2 had higher photocatalytic activity to degrade the dye. The CRD removal values for TiO2 and WO3 were 99.67 and 72.16 %, respectively, using 15 W, and the UV power did not have a significant effect on redox reactions according to the observations and the electrical energy consumption. The reaction kinetics study showed that the results obtained followed a first-order kinetics model. A mathematical model was developed based on the recycle ratio approach to study the effects of the recycle ratio and space-time on the Congo red dye removal through the different types of reactors. The simulated results showed that the ideal plug flow reactor performance gave the highest removal in less space-time than the recycle plug flow reactors. The recorded reactor performance decreased with the increasing recycling ratio, and the worst reactor performance was reported for the mixed-flow reactor.